1995
DOI: 10.7326/0003-4819-123-1-199507010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Misrepresentation of Academic Accomplishments by Applicants for Gastroenterology Fellowships

Abstract: Misrepresentation on applications for gastroenterology fellowships was common. The following steps are recommended: 1) Fellowship programs should require that copies of all publications and letters of acceptance for manuscripts in press be submitted with fellowship applications; 2) applications should contain a statement to be signed by the applicant that the information provided is accurate; 3) persons writing letters of recommendation should verify the information being submitted by applicants; 4) medical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…These findings of scientific misconduct by those entering medical disciplines are interesting in light of a number of other studies that have reported cheating among medical students 33 and medical school applicants. 34 Others have asked whether cheating is more common among medical students than other prescience majors. 35 Relative to the total population of students, medical students are proportionally more highly represented than non-medical students seeking graduate degrees when findings of misconduct are made.…”
Section: Allegations Against Graduate Studentsmentioning
confidence: 99%
“…These findings of scientific misconduct by those entering medical disciplines are interesting in light of a number of other studies that have reported cheating among medical students 33 and medical school applicants. 34 Others have asked whether cheating is more common among medical students than other prescience majors. 35 Relative to the total population of students, medical students are proportionally more highly represented than non-medical students seeking graduate degrees when findings of misconduct are made.…”
Section: Allegations Against Graduate Studentsmentioning
confidence: 99%
“…The experiences of Panicek et al [1] and others [2] have ensured that the CVs of applicants for any type of position will increasingly be critically evaluated for content accuracy rather than taken at face value, as many were previously. Plan ahead, check and recheck details, and seek the advice and re view ofpeers before sending out your CV.…”
Section: Employmentand Personalreferencesmentioning
confidence: 99%
“…Reasons for such misrepresentations can only be speculated and may include a desire to appear more competitive, combined with the knowledge that detection is unlikely, a lack of attention to detail, carelessness, or assuming that ''everybody does it.'' 1,[4][5][6] Regardless of the cause, the problem does exist and should be addressed by program directors, as integrity and attention to detail are characteristics that should be expected in our resident physicians.…”
mentioning
confidence: 99%
“…1,[5][6][7][8][9][10] This would be a possibility due to the inherent disadvantage of applying to a US residency position as an FMG, and perhaps added pressure to appear more competitive. 5 Furthermore, foreign journals are not as readily accessed by Western data searches.…”
mentioning
confidence: 99%
See 1 more Smart Citation